Psychology of reasoning : theoretical and historical perspectives - Manktelow, K. I., 1952-; Chung, Man Cheung, 1962- (Psychology Press, 2004)
This collection brings together a set of specially commissioned chapters from leading international researchers in the psychology of reasoning. Its purpose is to explore the historical, philosophical and theoretical implications of the development of this field. Taking the unusual approach of engaging not only with empirical data but also with the ideas and concepts underpinning the psychology of reasoning, this volume has important implications both for psychologists and other students of cognition, including philosophers. Sub-fields covered include mental logic, mental models, rational analy.